FACTORS FOR THE DEVELOPMENT OF DIDACTIC ADAPTATION TO THE CREDIT-MODULE SYSTEM IN YOUNG TEACHERS (TAMADDUN NURI JURNALI, 2024)
This article provides information on the development factors of didactic adaptation of young teachers to the credit-module system, pedagogical training, professional development opportunities, institutional support, availability of educational resources, mentoring programs, and individual characteristics of teachers. These factors contribute to the successful integration of young teachers into the credit-module system.